Interactions between Graphene‐Based Materials and Water Molecules toward Actuator and Electricity‐Generator Applications. Issue 10 (25th July 2018) - Xu, Tong; Han, Qing; Cheng, Zhihua; Zhang, Jing; Qu, Liangti
Abstract: The surface and interface interactions between water molecules and graphene or chemically modified graphene (e.g., graphene oxide) will enable changes of the physical and/or chemical state of graphene‐based materials, thus leading to many fascinating and unconventional phenomena with potential applications in various areas. The rise of novel energy‐conversion devices based on the interactions between graphene‐based materials and water molecules have triggered rapidly increasing research interest in the last few years, especially in deformable actuators and power generators. Here, the recent progress in tailored graphene‐based systems for moisture‐triggered actuation and electric generation by penetrating or flowing water, waves, or rain, in both the theoretical and experimental fronts, is summarized. The promising applications and the current challenges of the interactions between graphene‐based materials and water molecules for actuation and electricity generation are also discussed. Abstract : Interactions between graphene with water molecules can effectively induce the generation of electric and mechanical energy. The recent advances in graphene–water‐molecules interaction systems, including moisture‐triggered deformable actuators and water‐enabled electric generators are summarized.